2020
DOI: 10.1108/jwl-04-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

In-field training in the police: Learning in an ethical grey area?

Abstract: Purpose Although workplace learning is an important part of professional learning, little is known about the unethical aspects of workplace learning. This study aims to describe students’ learning experiences from in-field training in the police. This paper aims to examine how workplace learning can challenge proper ethical professional development and thus become a question of ethical concern. Design/methodology/approach The study is based on open-ended questions in a questionnaire among Norwegian police st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This understanding reflects what Håland and Tjora (2006, p. 996) claim to be work-oriented and grounded in the phenomenological, humanistic-and social constructivist perspective. This last implies that competence is defined and developed from workplace-and life-long learning (see Lave & Wenger, 2011;Gherardi & Nicolini, 2002;Hoel & Christensen, 2020). Competence is developed through participation both within and outside of (e.g.…”
Section: Theoretical Considerations On the Concept Of 'Competence'mentioning
confidence: 99%
See 1 more Smart Citation
“…This understanding reflects what Håland and Tjora (2006, p. 996) claim to be work-oriented and grounded in the phenomenological, humanistic-and social constructivist perspective. This last implies that competence is defined and developed from workplace-and life-long learning (see Lave & Wenger, 2011;Gherardi & Nicolini, 2002;Hoel & Christensen, 2020). Competence is developed through participation both within and outside of (e.g.…”
Section: Theoretical Considerations On the Concept Of 'Competence'mentioning
confidence: 99%
“…A shared characteristic of these studies (Chan et al, 2003;Finstad, 2000;Hoel, 2011;Edvardsen, 2019) is how the police officers' experiences and actions express 'competence-in-use' . Although competence derived from experience and mediated as a process (the phenomenological, humanistic-and social constructivist perspective) can ensure sound ethical practice (see Hoel, 2011;Hoel & Christensen, 2020;Martin & Staines, 1994cited in Garavan & McGuire, 2001, this perspective is not valued in the bulk of literature discussing competence (Ellström & Kock, 2008;Lindberg & Rantalao, 2014).…”
Section: Theoretical Considerations On the Concept Of 'Competence'mentioning
confidence: 99%
“…In order to prepare for the job, police recruit programs around the world regularly entail three planned learning settings: (a) theory informing class-room settings at the police academy, the police college, or the police university (Frevel, 2018;Leek, 2020); (b) practical skills training like conflict management training, traffic stop training, etc., ; and work-integrated learning through supervised and accompanied working in the field, otherwise known as fieldtraining (Engelson, 1999;Hoel and Christensen, 2020).…”
Section: Learning For the Jobmentioning
confidence: 99%
“…Field-training officers-like police trainers-are role models and peers and are of critical importance for police learning (Belur et al, 2019;Staller et al, 2022a). They can be a source of ethical practice but also of unethical practice (Fekjaer et al, 2014;Hoel and Christensen, 2020). For example, the study on police students by Fekjaer et al (2014) showed that, during field training, police students changed their attitude to be more in line with negative characteristics of street cop culture.…”
Section: Learning For the Jobmentioning
confidence: 99%
“…For example, police institutions have a clear hierarchy and chain of command. A recruit in training can be at risk of “behaving like his field training officer wants the behavior to be seen” (Hoel and Christensen, 2020) and might not challenge these views. As such, managerial authority may create a source for bias.…”
Section: Sources Of Cognitive Biases In Police Conflict Managementmentioning
confidence: 99%